Radiation-induced defect's clustering and self-organization during surface modification - Bondareva, A.L.; Zmievskaya, G.I. (Вопросы атомной науки и техники, 2006)
Defects' clustering model is applied to study of the both: helium blistering in metal lattice and a thin film islands deposition. Plasma surface modification is investigated as a first order phase transition at a fluctuation stage. Wiener stochastic processes which are associated with the clustering evolution as well as with the defects motion are used. Brownian motion due to a long-distance potentials of indirect interaction blisters (or islands): through acoustic phonons and Friedel's oscillations of lattice's electronic density has been modeled. Stochastic simulation has involved the analyse of a follows self-organization structures: vacancy-gaseous bubbles layers (or porosity) and islands chains on the surface with roughnesses.